Déterminisme du recrutement larvaire de l’huître creuse (Crassostrea gigas) dans la lagune de Thau. - Lagarde, Franck; Fiandrino, Annie; Richard, Marion; Bernard, Ismael; Mortreux, Serge; Ubertini, Martin; Chiantella, Claude; Boj, Marie; Meddah, Slem; Leurion, Axel; Soriano, Solenn; Fuhrmann, Marine; et al. (2015)
Since spat mortality events that were firstly detected in 2008, Mediterranean shellfish industry seeks to exploit the Pacific oyster spat from lagoon natural recruitment. The CRCM, Cepralmar and Ifremer developed accordingly a research project named PRONAMED Phase 1 and 2 - 2010-2014, in order to define the economic potential of spatfall and improve knowledge of the reproductive cycle of Crassostrea gigas in this specific environmental context. The results of the past three year‘s study (2012, 2013, 2014) showed that broodstock have the ability to provide larvae after sexual maturation and spawning. A coincidence was noted between moon phase (new and full moon) and spawnings with an amplifying effect of storms on the intensity of spawning (Ubertini et al. In prep). The works exposed here focus on larval cycle and spat recruitment. The results showed that larval development until pediveliger settlement, influenced by water temperature and abundance of Chaetoceros sp, faced no major biological lock. The supply of larvae from different areas of the lagoon has been governed by hydrodynamics and a new method of lagoon larval connectivity assessment was thus developed: the dynamic connectivity. A good fit was noted between high dynamic connectivity areas and the most effective collection stations (Lagarde et al. 2015). It was shown that survival, during metamorphosis, relied on the abundance of total nanophytoplankton (pico + nanophytoplankton). Moreover, shellfish farming areas were less efficient for spat collection that some others located off shellfish farms (Lagarde et al. 2015). An additional experiment on collectors management showed that their deployment in growing area under the condition of dewatered, arranged in line, horizontally, led to the best results. This report is a first work of exploration, explanation and synthesis on reproduction and larval recruitment determinism of the Pacific oyster in Mediterranean lagoon. The abilities of Thau lagoon to provide oyster spat has been explored and now the next ...